Evaluation of the Effectiveness of Clinical Pharmacists’ Consultation in the Treatment of Infectious Diseases: A Single-Arm, Prospective Cohort Study - Zhang, Jiaxing; Qian, Xin; Zhang, Lingmin; Hu, Linfang; Fan, Lingyan; Wang, Qingchen; Lan, Bo; Sheng, Changcheng; Li, Li; Zheng, Wenyi; Xie, Juan (Frontiers in Pharmacology, 2019)
Background: With the implementation of Antimicrobial Stewardship Program, clinical pharmacists’ consultation (CPC) for infectious diseases (ID) is gradually adopted by many hospitals in China. We conducted a cohort study to evaluate the effectiveness of CPC in ID treatment on patient outcomes and potential determinants. Methods: Based on a registry database, a prospective cohort study was conducted in Guizhou Provincial People’s Hospital. The main exposure factor was whether clinician adopted the suggestion from clinical pharmacist. The outcome was effective response rate (ERR) of ID patients. The variables associated with the outcome (e.g. age, gender, severity of infection, liver function, and kidney function) were also prospectively recorded. A multilevel model was performed to analyze the factors related to ERR. Results: A total of 733 ID inpatients were included in the final analysis according to the predesigned inclusion and exclusion criteria. The proportion of clinical pharmacists’ suggestions adopted by clinicians and ERR were 88.13% and 69.03%, respectively. Significant data aggregation (P < 0.05) for individuals at the level of department was observed. According to the two-level variance component model, liver dysfunction (Adjusted Odds Ratio (AOR) = 0.649, 95%Credible Interval (CI): 0.432 0.976), severity of infection (AOR = 0.602, 95%CI: 0.464 0.781), and adopting the suggestion from pharmacist (AOR = 1.738, 95%CI: 1.028 2.940) had significant association with ERR. Conclusions: Our study suggests that the effect of CPC on ID treatment is significant. The policy/decision makers or hospital managers should be cognizant of the critical value of clinical pharmacists in ID treatment.